2023
DOI: 10.1007/s10113-023-02025-2
|View full text |Cite|
|
Sign up to set email alerts
|

Translating and embedding equity-thinking into climate adaptation: an analysis of US cities

Abstract: Cities increasingly recognize the importance of furthering social equity in their climate adaptation planning. Such efforts are often in response to grassroots mobilizations, yet it is not clear to what extent they translate into urban coalitions, policy designs, and implementation efforts within city governments. In this paper, we respond to this knowledge gap by assessing how equity-thinking is translated into cities’ adaptation decision-making and governance arrangements, especially in ways that can lead to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…A report published by the Michigan Climate Action Network (MiCAN) served as a starting point to identify municipalities with local climate plans (49). According to the report, sixteen municipalities in the state had climate action policies and renewable energy goals as of 2022.…”
Section: Methodsmentioning
confidence: 99%
“…A report published by the Michigan Climate Action Network (MiCAN) served as a starting point to identify municipalities with local climate plans (49). According to the report, sixteen municipalities in the state had climate action policies and renewable energy goals as of 2022.…”
Section: Methodsmentioning
confidence: 99%
“…Many of the studies we analyzed discussed the content of climate adaptation plans, particularly how cities are including considerations of equity and justice in their planning documents (Schrock et al 2015, Fainstein 2018, Meerow et al 2019, Chu and Cannon 2021, Fiack et al 2021, Hess and McKane 2021, Mullenbach and Wilhelm Stanis 2022, Cannon et al 2023. One study also analyzed reports from different organizations about how cities can enhance equity and justice in their plans (Shi 2021).…”
Section: Methods Usedmentioning
confidence: 99%
“…The studies encompassed in this review indicate that cities are quite good at identifying their problems, but struggle when it comes to explaining their long-term goals, particularly related to equity and justice implications. Our analysis revealed that cities often describe the types of goals they have in many areas, but researchers of these cities struggled to identify implementation timeframes, funding source, guidelines, and responsible parties (Cannon et al 2023). Additionally, when considering the three prongs of EJ theory, study authors indicated plans least often discussed issues related to recognition justice and acknowledging how systemic racism has shaped their present conditions, though our sample indicated that many cities were able to identify which groups of people were considered vulnerable (Meerow et al 2019, Cannon et al 2023.…”
Section: What Do the Plans Say?mentioning
confidence: 99%
“…A larger discrepancy between differently sized municipalities can be seen with regards to the reduction of social inequalities, which is an important motivation for adaptation policy development in more than half of the large municipalities but only in 14% of the medium-and small-sized municipalities. This may suggest that equity concerns in climate change adaptation, which have increasingly spread across larger cities (see Cannon et al 2023) may not as easily gain traction in smaller municipalities. About half of the medium-sized and large municipalities also see local political pressures as an important motivation for adaptation activities while this is only the case in about 25% of the small municipalities.…”
Section: Internal and External Motivationsmentioning
confidence: 99%